Etiology, Laboratory and Clinical Course of Elevated Transaminases in Pediatric Emergency Department - Anıl Er; Sevim Çakar; Nebahat Ermiş; Duygu Özkerim; Aykut Çağlar; Tanju Çelik; Hurşit Apa (Galenos Yayinevi, 2021)
Introduction:Elevated transaminases has been frequently observed in pediatric emergency department admissions due to increasing utilization of routine laboratory packages. There are limited data about clinical features, underlying conditions and clinical course of these patients. This study aims to evaluate clinical characteristics, etiologies, recovery time and length of stay in hospital of children with elevated transaminases in pediatric emergency department.Methods:We included 1-month- 18-year-old children who were followed in observation unit of Pediatric Emergency Department of University of Health Sciences Turkey, Dr. Behçet Uz Pediatrics and Surgery Training and Research Hospital and had increased transaminases between 2016 January and 2017 January. Increased aspartate aminotransferase and alanine aminotransferase were defined as values above 60 U/L and 45 U/L. The clinical and laboratory data were obtained retrospectively from electronic medical records.Results:We included 89 patients. The median age was 36 months (1-216 months). The most common symptoms were vomiting (n=31), fever (n=27) and abdominal pain (n=25), the most frequent physical examination finding was dehydration (n=20). Etiologies were infections (40.5%), metabolic disorders (11.2%), drug induced liver injury (9.0%), hepatobiliary diseases (5.6%), others (9.0%) and unexplained in 24.7%. Transaminases were elevated under 5 times in 62.5%. N-acetylcystein and ursodeoxycolic acid were administered in 9.0% and 18.0%. The median recovery time was 5 days (1-61 days) and length of stay was 3.7±9.2 days. Recovery time and length of stay were not significantly different according to etiologies (p=0.107 and p=0.952).Conclusion:This study has indicated that mild elevation of transaminases is common in pediatric emergency department. Although most common reason is infections, it can be related to various conditions such as trauma and inherited metabolic disorders. Also, we have found that the recovery time is short and does not change according to etiologies. However, multi-center studies in a large population are still required to form algorithms for the assessment of elevated transaminases in pediatric emergency department .